2015
DOI: 10.4103/0974-2700.166590
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, causes and pattern of abdominal trauma: A 4-year descriptive analysis

Abstract: Background:The incidence of abdominal trauma is still underreported from the Arab Middle-East. We aimed to evaluate the incidence, causes, clinical presentation, and outcome of the abdominal trauma patients in a newly established trauma center.Materials and Methods:A retrospective analysis was conducted at the only level I trauma center in Qatar for the patients admitted with abdominal trauma (2008-2011). Patients demographics, mechanism of injury, pattern of organ injuries, associated extra-abdominal injuries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 21 publications
4
34
3
Order By: Relevance
“… 30 A study conducted by Arumugam et al demonstrated that liver is the most common organ involved followed by the spleen. 31 Most of the traumas were managed conservatively and only a few patients were hemodynamically unstable and underwent emergency exploratory laparotomy, a result consistent with other research studies. 32 …”
Section: Discussionsupporting
confidence: 83%
“… 30 A study conducted by Arumugam et al demonstrated that liver is the most common organ involved followed by the spleen. 31 Most of the traumas were managed conservatively and only a few patients were hemodynamically unstable and underwent emergency exploratory laparotomy, a result consistent with other research studies. 32 …”
Section: Discussionsupporting
confidence: 83%
“…The overall median duration of hospital stay in the present study was 5.83 days which is lower than reported by Arumugan et al [1] and Chalya et al [6]. In comparison to other studies, mortality rates of 12.5% and 26% reported respectively by Musau P. et al [29] and Mohamed AA et al [30], overall mortality rate among abdominal trauma patients in our series was very low 2%.…”
Section: Discussioncontrasting
confidence: 65%
“…Trauma continues to be a major public health problem worldwide. Abdominal trauma (AT) is usually associated with high morbidity and mortality [1]. It may be blunt or penetrating and may involve damage to the abdominal organs.…”
Section: Introductionmentioning
confidence: 99%
“…Hemodynamic instability is the primary indication for OM [ 14 , 17 , 18 ]. The objective of this study is to examine the prevalence, clinical presentation, management and outcomes of patients sustained blunt liver injuries in a small rapidly developing country in the Middle East.…”
Section: Introductionmentioning
confidence: 99%